La prostitución de las mujeres a nivel nacional e internacional y la igualdad de género. - Gallegos Guerra, Alex David (2023)
The purpose of this project is to carry out an investigation in the city of Quito, Province of Pichincha, and online throughout the national territory, in the period from January to March 2023, regarding the existence of the affiliation of people dedicated to prostitution, to the Ecuadorian Institute of Social Security, and if the workers are not affiliated, identify the reasons for this, either due to social stigma, failures in the legislation or lack of legal advice. The present investigation also seeks to compare the regulation of the activity of prostitution, with other countries in South America, and the world, and if there are better conditions in other places, identify possible improvements and propose changes to national legislation or otherwise, a legal guide aimed at training sex workers, which can also be used by other independent workers. The National Constitution of 2008 establishes in its article 11 numeral 2 that in the exercise of rights "All people are equal and will enjoy the same rights, duties and opportunities." (Constituent Assembly, 2008) and in its article 33, the constitutional text adds that "The State will guarantee to working people full respect for their dignity, a decent life, fair wages and compensation and the performance of a healthy and freely chosen job. or accepted.” (Constituent Assembly, 2008). That is, people may engage in the economic activity of their choice as long as it is not prohibited and the regulations of the law are complied with. Therefore, said economic activity cannot be classified as a crime. Likewise, the Social Security Law (2001) establishes in its article 1 its principles, among which is that of solidarity, which is: "Aid among all insured persons, regardless of nationality, ethnicity, place of residence, age, sex, state of health, education, occupation or income, in order to jointly finance the basic benefits of the Compulsory General Insurance." (National Congress of Ecuador, 2001) The Social Security Law (2001) establishes that any person, regardless of the economic activity to which they are engaged, or their income, can collaborate 5 to finance the activities of the IESS and in turn be protected by it. And in its article 2 it adds the "subjects of protection" Subjects "obliged to request protection" of the Compulsory General Insurance, as affiliates, are all persons who receive income from the execution of a work or the provision of a physical or intellectual service, with or without employment relationship; in particular: b. The self-employed worker (National Congress of Ecuador, 2001) Therefore, the question arises if this sector of workers is subscribed to Social Security, which according to article 3, could benefit them by protecting them from the following risks: a. Disease; b. Maternity; c. Work risks; d. Old age, death, and disability, which includes disability; and, e. Unemployment Keywords: Prostitution, Social Rights, Crimes, Labor Rights